Germany is looking for foreign labour: How to make recruitment development-orientated, sustainable and fair - Steffen Angenendt; Nadine Knapp; David Kipp (Stiftung Wissenschaft und Politik (SWP), 2023)
Germany's shortage of skilled workers has sharply increased, especially in the social and education sectors, health and care, construction and skilled crafts, information technology and jobs in science, technology, engineering and mathematics (STEM). Simultaneously, the demand for low qualified labour has also been growing, for instance in help and household-related services. While EU member states continue to be the source for the majority of labour migration, their migration potential is declining due to their similarly ageing and shrinking populations. Recruiting workers from third countries, including Germany's development partner countries, will become of strategic importance. In spite of many recent reforms, the recruitment of workers from third countries is still inadequate, and not enough attention has so far been paid to development policy aspects. Germany's recruitment activities need to be more closely embedded in fair, development-orientated partnerships with countries of origin, in which their interests are taken into account and the rights of migrant workers are respected. Since many industrialised countries now recruit workers, this could also be a competitive advantage for Germany. The German government should make use of the extensive experience gained from the pilot projects to attract skilled workers for large-scale recruitment programs. These projects will require the systematic cooperation of all relevant ministries (whole-of-government approach) as well as the involvement of civil society and the private sector to set the course for development-orientated recruitment. The German government should engage even more strongly in the relevant global processes and forums whilst advocating fair recruitment.
Keywords: 320; skilled workers; labour migration; demographic potential; Skilled Immigration Act (FEG); medical health jobs; language skills; qualifications; recruitment